Illustrated entertainment. Correo del Domingo (1864-1868) and the consolidation of the illustrated press in Buenos Aires (Quinto Sol, 2021)
Since the beginning of the 21st century, a bibliography on the printed image in 19th century Buenos Aires has been consolidated. However, Correo del Domingo (1864-1868) has not yet been the object of a long-term research, even though the publication founded by José María Cantilo, along with El Mosquito (1863-1893), made the 1860s a turning point in the history of the local illustrated press.In this article we will concentrate on the analysis of the editorial configuration of the weekly publication. We identify as its greatest formal innovation the fact that it brought together different resources, which could be found years before in the newspaper's feuilleton or in literary publications, converging in a periodical that made a qualitative leap in the experience of reading the press and opened a path that would culminate in the turn-of-the-century magazine. Specifically, we will analyze how discursive genres associated until then to the newspaper's rezde-chausée (in particular, the serialized novel) were incorporated into the weekly format, as well as an unprecedented display of lithographic images, throughout a generous publication that multiplied the usual four pages of the contemporary press to attract an expanded and diversified readership.
Keywords: periodic press lithograph serial novels readers; periodic press; lithograph; serial novels; readers